Reduced RANBP9 expression is associated with poor prognosis in colorectal cancer patients - Wu, Guangbin; Li, Ji; Qin, Chunzhi (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Colorectal cancer (CRC) is the third most common malignancy worldwide. RANBP9 is a RAN-binding protein that has been reported to be a reliable predictor for prognosis in some human cancers. The mechanism of RANBP9 involvement in CRC carcinogenesis is unknown. This study measured RANBP9 expression levels in CRC to determine its association with clinicopathological parameters. Methods: This study included 228 CRC patients who underwent radical resection. RANBP9 expression was determined using immunohistochemistry. Based on follow-up data, the correlation of RANBP9 expression levels with clinicopathological parameters, including disease free survival (DFS) and overall survival (OS) was evaluated. Results: Reduced RANBP9 expression was correlated with tumor location (P=0.014), vascular invasion (P=0.057) and normal serum carcinoembryonic antigen levels (P=0.001). Patients with reduced RANBP9 expression had a 5-year DFS rate of 63.0% compared to 78.9% for patients with high expression levels of RANBP9 (P=0.015). Subgroup analysis demonstrated that reduced RANBP9 expression was significantly correlated with a worse DFS rate (P=0.037) for patients with left-sided colon cancer. RANBP9 was found to be an independent predictive factor for estimating DFS rate (P=0.029, hazard ratio: 0.580, 95% confidence interval: 0.356–0.946) and OS. Conclusions: RANBP9 expression levels is a potential prognostic factor for estimating CRC survival rates in patients after surgery.